The Fornax deep survey with VST. II. Fornax A: a two-phase assembly caught on act - Iodice, Enrichetta; Lisker, Thorsten (Arxiv, 2017)
As part of the Fornax Deep Survey with the ESO VLT Survey Telescope, we present new